Effects of Fermentation by Yeast and Amylolytic Lactic Acid Bacteria on Grain Sorghum Protein Content and Digestibility - Christina N. Day; Ruben O. Morawicki (Journal of Food Quality)
Despite many advantages to its cultivation, grain sorghum is an underutilized crop because of low nutrient availability, particularly protein digestibility, due to antinutritional compounds in the grain and by moist-heat cooking. Some of these concerns can be mitigated by how the grain is processed. Fermentation is one processing method that can improve digestibility and at the same time concentrate protein in a substrate. In this experiment, grain sorghum was subjected to different treatments and fermented with baker’s yeast (Saccharomyces cerevisiae) and an amylolytic species, Lipomyces kononenkoae, to improve and increase protein content. The effects of pasteurization or sterilization of the substrate, nitrogen supplementation, amyloglucosidase addition, and coculture with Lactobacillus amylovorus were examined. After fermentation, baker’s yeast samples treated with enzyme increased in crude protein, from 9% in unfermented grain to approximately 27% after treatment. Nitrogen supplementation accelerated protein enrichment and was a significant factor at 24 hours of fermentation. Both types of yeast increased pepsin digestibility of sorghum protein compared to thermally processed control samples. The ratio of phytate to protein was reduced by both yeast species. L. kononenkoae reduced phytates in the substrate but did not enrich protein content. The lactic coculture had no significant effect on measured responses.